On the Nature of the Bright Front of Solar Coronal Mass Ejections - Hongqiang Song; Rui Wang; Leping Li; Bing Wang; Yao Chen (The Astrophysical Journal, 2025)
A new explanation has been proposed on the nature of the three-part (bright core, dark cavity, and bright front) structure of coronal mass ejections (CMEs). It suggests that the bright front originates from the plasma pileup along the overlying coronal loops rather than the boundary of the magnetic flux rope at the early eruption stage. This has been confirmed with an active-region event through the direct comparison between the EUV loops and the CME front. However, large-scale EUV loops are hardly observed outside of strong active regions; thus, the front nature remains unclear for CMEs from quiet-Sun regions or weak active regions. In this paper, we address this issue through an intermediate filament eruption from a plage region without sunspots on 2024 March 30. Combining the overlapping observations of the Atmospheric Imaging Assembly and K-Coronagraph, we find that the overlying coronal loops appear gradually in EUV images during the filament eruption. The compressed loops and the plasma pileup along the loops (171 Å) correspond to the CME front in white-light images, which is essentially similar to the situation of events from strong active regions. Therefore, we believe that the explanation on the CME front holds true regardless of whether the EUV loops are visible or not prior to the eruption, and it works for events from different regions, including active regions and quiet-Sun regions. The reasons why the density evolution with height does not support or deny the pileup are discussed.